The burden of food related ill health in the UK. - Rayner, M; Scarborough, P (2005)
STUDY OBJECTIVE: To quantify the burden of ill health in the UK that can be attributed to food (the burden of food related ill health). DESIGN: Review and further analysis of the results of work concerned with estimates of the burden of disease measured as morbidity, mortality, and in financial terms and with the proportion of that burden that can be attributed to food. MAIN RESULTS: Food related ill health is responsible for about 10% of morbidity and mortality in the UK and costs the NHS about 6 billion pounds annually. CONCLUSIONS: The burden of food related ill health measured in terms of mortality and morbidity is similar to that attributable to smoking. The cost to the NHS is twice the amount attributable to car, train, and other accidents, and more than twice that attributable to smoking. The vast majority of the burden is attributable to unhealthy diets rather than to food borne diseases.